2023
DOI: 10.1021/acsanm.3c00371
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Intense Violet-Emitting CsPbCl3 Nanocrystals for Light-Emitting Diodes: Directly Obtained by L-Type Surface Passivation

Abstract: Poor photoluminescence quantum yield (PLQY) and stability of the violet-emitting CsPbCl 3 NCs are responsible for the very low efficiency of the violet LEDs (<435 nm) based on these substances. Herein, we report a direct method of obtaining CsPbCl 3 NCs with exceptional characteristics employing diphenylphosphoryl chloride, which serves not only as an efficient chloride precursor but also prevents protonation of the amine ligand. High PLQY (∼87%) and remarkable stability of these NCs in a polar environment, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The final absolute PLQY was found to be exceptionally high (96 ± 5%). It is reasonable to suppose that the low ligand density allowed the passivation of the NC surface with L-type ligands (OLAm), thus limiting the nonradiative exciton recombination and improving the PL efficiency. , In fact, we observed a monoexponential PL decay (τ AV = 3.1 ± 0.2 ns, Table S1), probably resulting from the annihilation of the faster nonradiative recombination due to the OLAm copassivation of the NC surface (Figure E). Importantly, probably due to steric impediments, the amine excess does not impair the adhesion of the OPDA ligand via its proton abstraction, thus preserving the colloidal integrity of OPDA-CsPbBr 3 NCs in these conditions.…”
Section: Resultsmentioning
confidence: 86%
“…The final absolute PLQY was found to be exceptionally high (96 ± 5%). It is reasonable to suppose that the low ligand density allowed the passivation of the NC surface with L-type ligands (OLAm), thus limiting the nonradiative exciton recombination and improving the PL efficiency. , In fact, we observed a monoexponential PL decay (τ AV = 3.1 ± 0.2 ns, Table S1), probably resulting from the annihilation of the faster nonradiative recombination due to the OLAm copassivation of the NC surface (Figure E). Importantly, probably due to steric impediments, the amine excess does not impair the adhesion of the OPDA ligand via its proton abstraction, thus preserving the colloidal integrity of OPDA-CsPbBr 3 NCs in these conditions.…”
Section: Resultsmentioning
confidence: 86%
“…C–X bond activation represents a specific and intriguing area of photocatalytic organic transformation. ,, Recent research has demonstrated the ability to activate C–X bonds in alkyl halides via photoassisted anion exchange reactions using perovskites. ,, This light-controlled approach offers significant advantages, allowing for the reaction to be carried out under ambient conditions with near-perfect conversion. This paves the way for exciting possibilities beyond photocatalysis, extending to the potential use of perovskite NCs in light-emitting diodes for display technologies. …”
Section: Introductionmentioning
confidence: 99%
“…This may find exciting applications in fabricating violet LEDs (<435 nm). Violet LEDs suffer from weak luminescence due to reduced lattice stability, a wider band gap, and the formation of a high density of deep trap states due to chloride vacancies. As a result, they are less prominent commercially than red and green LEDs . Our approach can perhaps bypass the standard hot injection technique for synthesizing CsPbCl 3 NCs, omitting the need for a hazardous TOP ( n -trioctylphosphine) ligand to solubilize PbCl 2 .…”
Section: Introductionmentioning
confidence: 99%